The Stability of Plant Root-Soil Slope - Chen, Chunxiao (International Journal of Management and Education in Human Development, 2023)
In this paper, taking a highway in Guangxi as the research background, it is proposed to use the vegetation root system to reinforce the road slope. However, the design method of the vegetation root system reinforcement slope is not yet mature. Therefore, this paper attempts to carry out experimental research on the strength parameters of plant rootsoil, to provide valuable experimental data for the design of vegetation-reinforced slopes. Combined with the traditional slope stability analysis method, the design calculation method of the slope reinforced by plant roots is finally obtained. Therefore, based on the climate and soil conditions in Guangxi, this paper selects suitable slope protection plants according to local conditions and then conducts a direct shear test to determine the cohesion and internal friction angle of the plant root-soil composite soil. Using the arc strip method, like Lizheng software, and the BP neural network method, the strength parameters of the root-soil are input, and the stability of the slope is checked, so the design calculation method of plant root reinforcement slope is obtained.